Viability of heat treated microspores of Cocos nucifera L. for induction of microspore embryogenesis - S. P. N. C. Jayarathna; H. G. M. R. Suraweera; N. K. L. S. Piyatissa; P. I. P. Perera; V. R. M. Vidhanaarachchi (International Coconut Community Journal, 2025)
Tall coconut (Cocos nucifera L.) palm is an allogamous and highly heterozygous which is a major obstacle for conventional breeding. Microspore embryogenesis is a promising method which enables the development of homozygous lines. This study is conducted to detect the coconut microspore viability after heat treatment with different incubation periods for the induction of embryogenesis. Anthers were collected from the inflorescences of two coconut palms at three weeks before splitting stage and microspores were extracted. They were subjected to heat treatment for 1, 3, 6 and 9 days either prior or post inoculation. Viability was tested using iodine potassium iodide, acetocarmine and 2, 3, 5- triphenyltetrazolium chloride. Induction of embryogenesis after subjecting to the heat treatment was also studied. Cultures were initiated in modified Eeuwens Y3 medium. To observe the nuclear status of microspores, the samples were stained with 1% acetocarmine after 7 and 14 days. The callus formation was also recorded. A significant difference in viability was observed between control, heat treated prior inoculation and post inoculation when observed in day 01, day 07 and day 14. Significant difference in viability was not detected with no incubation (I0) and 01-day incubation (I1) when microspores were observed in 01 day and 07 days whereas, 3-day incubation (I2), 6-day incubation (I3) and 9-day incubation (I4) resulted significantly different viability of microspores when observed in 01 and 07 day after culturing. Viability of microspores were significantly different for all incubation periods 14 days after culturing. Result was similar with the three stains used to test viability after testing in 1, 7 and 14 days. The highest frequency of binuclear (58.5%) and tetra nuclear (7.2%,) microspores were recorded in the samples treated after culturing the microspores. The multinuclear stages of microspore indicated the induction of embryogenesis. The most effective heat treatment was 38 °C for 3 days after inoculation of the microspores. The results of the study are important for further improvement of microspore embryogenesis protocol.